Psychological Inflexibility and Loneliness in Young Adults: The Role of Hope as a Mediator - Sevinawati, Elnia; Oriza, Imelda Ika Dian (Universitas Medan Area, 2023)
Young adulthood (18-29 years of age) is the most unstable period of the life span when changes in intimate relationships and work are the common issues. This period is closely related to various mental health problems, such as loneliness. This study aims to determine the role of hope as a mediator between psychological inflexibility and loneliness in young adults. Research participants were 230 participants who were in the young adulthood stage (18-29 years of age). Loneliness was measured using UCLA Loneliness Scale-6 (ULS-6), psychological inflexibility was measured using Acceptance and Action Questionnaire (AAQ-II), and hope was measured using The Adult Dispositional Hope Scale (AHS). Mediation analysis was done using Hayes PROCESS MACRO (Model 4). The results of the analysis show that hope has a mediating role in the relationship between psychological inflexibility and loneliness in young adults. The implication of this research is that it can be used as a consideration for selecting interventions that focus on increasing psychological flexibility and hope when dealing with loneliness in young adults.